2016
DOI: 10.1139/cjpp-2015-0112
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferation effects of Cistanches salsa on the progression of benign prostatic hyperplasia

Abstract: Cistanche salsa has been used in traditional medicine for the treatment of kidney deficiency, neurasthenia, sexual dysfunction diseases, and benign prostatic hyperplasia (BPH). The aim of this study was to investigate the mechanism by which C. salsa extract (CSE) elicits an anti-proliferative effect on the prostate tissue of BPH-induced rats. The effects of CSE on BPH were evaluated in terms of prostate weight, production of serum dihydrotestosterone (DHT), and the mRNA expression of 5α-reductase type 1 and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Certain major active components of GGN, including quercetin, kaempferol, coumarins and lignin glycosides, have been previously reported to exhibit anti-inflammatory and anti-oxidative qualities (18)(19)(20)(21). Furthermore, a recent study by our group revealed that Cistanche salsa extract elicits an anti-proliferative effect on the prostate tissue of rats with BPH (22). Although studies on the physiological functions of the major active components of GGN have been performed, the molecular mechanism(s) underlying the effect of GGN on BPH have not yet been investigated; therefore, the aim of the present study was to assess the anti-proliferative effects of GGN in a testosterone-induced rat model of BPH, and to demonstrate that it functions through regulation of the inflammatory response and apoptotic protein expression.…”
Section: Introductionmentioning
confidence: 91%
“…Certain major active components of GGN, including quercetin, kaempferol, coumarins and lignin glycosides, have been previously reported to exhibit anti-inflammatory and anti-oxidative qualities (18)(19)(20)(21). Furthermore, a recent study by our group revealed that Cistanche salsa extract elicits an anti-proliferative effect on the prostate tissue of rats with BPH (22). Although studies on the physiological functions of the major active components of GGN have been performed, the molecular mechanism(s) underlying the effect of GGN on BPH have not yet been investigated; therefore, the aim of the present study was to assess the anti-proliferative effects of GGN in a testosterone-induced rat model of BPH, and to demonstrate that it functions through regulation of the inflammatory response and apoptotic protein expression.…”
Section: Introductionmentioning
confidence: 91%
“…It may be a potential therapeutic candidate for benign prostate hyperplasia (BPH) owing to its ability to decrease prostate weight, serum dihydrotestosterone (DHT) concentration, and mRNA expression of 5α-reductase type 1 and type 2 in prostate tissue of BPH-induced rats. It also suppressed cell proliferation by regulating the expression levels of inflammatory-related proteins (inducible NO synthase and cyclooxygenase 2) and apoptosis-associated proteins (caspase-3 and Bcl-2 family proteins) [ 119 ].…”
Section: Extractions or Bioactive Components With Potential Anti-amentioning
confidence: 99%
“…195) C. salsa extracts also showed antiproliferative effects on benign prostatic hyperplasia rats by regulating inflammatory cytokines or depressing apoptosis-associated proteins, which was proven by Korean researchers. 196) In 2007, Hausmann et al from Germany proved that PhGs could alleviate intestinal inflammation in dextran sulphate sodium-induced colitis. 197) Researchers from Australia and Greece found compound 2 could alleviate intestinal mucositis in mice by preventing in-flammationin2015.…”
Section: Anti-inflammation Activitiesmentioning
confidence: 99%